A Guide to Neonatal and Pediatric ECGs - Galli, Maria Albina. (Springer Milan : Imprint: Springer, 2013)
Electrocardiography has an ever-expanding role in pediatric cardiology evaluation. The specific competencies required for its optimal use in this setting, however, generally lie beyond the expertise of cardiologists used to dealing with adults. This guide the product of extensive practical experience in the field of pediatric cardiology proposes a very simple method for reading neonatal and pediatric ECGs that is based on the application of straightforward criteria and permits the immediate recognition of normal and pathological patterns. The first part of the guide presents and describes this methodology and the parameters of normal pediatric ECGs, while the second part focuses on specific pediatric anomalies. More than 150 ECGs displaying both normal and pathologic findings are included, all of which have been collected from clinical practice and analyzed using the proposed method. This book will be an invaluable reference tool for all cardiologists who deal with newborns and children.